Ratios can be misleading for detecting selection - Kratochvíl, Lukáš; Rovatsos, Michail (Current biology, 2022)
Lukáš Kratochvíl and Michail Rovatsos respond to the recent study by Thibault Leroy and colleagues on island songbirds.
Keywords: Animals; zvířata; zpěvní ptáci; Songbirds